Research on Technology Competencies in EFL Language Instructors: Technology-Pedagogy-Content in Language Teaching - Rodrigo Tovar Viera; Diego Ismael Velasco Sánchez (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Background:Living in the digital era where the information and communication technologies (ICTs) have extensively changed the way of teaching, language instructors, in particular, should be computer literate to put their technical knowledge into practice in such a way they effectively integrate technology into language learning classrooms.Methodology:The research contextualizes teachers’ beliefs and competencies of using the Technological Pedagogical Content Knowledge (TPCK) in teaching English as a foreign language. The study is an extension of previous research carried out by Tovar et at., (2019), and Tovar (2019). It applied a survey-based questionnaire, an unstructured interview, and classroom observations for data collection. The assessment instruments were administrated to EFL language instructors, who work in the Language Center at the Technical University of Cotopaxi.Findings:Results revealed that a high percentage of the EFL language instructors are not familiar with the use of the TPCK model and its integration into their classroom practices. This support the claim that teachers probably have technological knowledge, but they are not well-prepared to combine teaching resources and appropriate pedagogical methods for language teaching and learning.Conclusions:The study hopes that research outcomes arise linguistic implications and pedagogical applications for developing teachers’ TPCK competencies when integrating technology in EFL classroom settings. Limitations, as well as considerations for further research, are discussed.